2014
DOI: 10.1002/humu.22698
|View full text |Cite
|
Sign up to set email alerts
|

Nonsense Mutation in Coiled-Coil Domain Containing 151 Gene (CCDC151) Causes Primary Ciliary Dyskinesia

Abstract: Primary ciliary dyskinesia (PCD) is an autosomal-recessive disorder characterized by impaired ciliary function that leads to subsequent clinical phenotypes such as chronic sinopulmonary disease. PCD is also a genetically heterogeneous disorder with many single gene mutations leading to similar clinical phenotypes. Here, we present a novel PCD causal gene, coiled-coil domain containing 151 (CCDC151), which has been shown to be essential in motile cilia of many animals and other vertebrates but its effects in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 12 publications
2
25
0
Order By: Relevance
“…CCDC151 , which is required for the function of intraflagellar transport‐dependent motile cilia, is a novel gene with a limited number of related studies . Several studies reported that CCDC151 mutations were associated with primary ciliary dyskinesia . CHRNB2 is an acetylcholine receptor subunit whose mutations are associated with autosomal dominant nocturnal frontal lobe epilepsy .…”
Section: Discussionmentioning
confidence: 99%
“…CCDC151 , which is required for the function of intraflagellar transport‐dependent motile cilia, is a novel gene with a limited number of related studies . Several studies reported that CCDC151 mutations were associated with primary ciliary dyskinesia . CHRNB2 is an acetylcholine receptor subunit whose mutations are associated with autosomal dominant nocturnal frontal lobe epilepsy .…”
Section: Discussionmentioning
confidence: 99%
“…As aforementioned, the participating family was previously analysed for a PCD study [ 3 , 4 ]; and this study was carried out after the family re-attended the clinic enquiring about the cause of PLS present in other siblings within the family.…”
Section: Methodsmentioning
confidence: 99%
“…a tenth will be variants with ‘predicted high impact’ (also known as Φ variants i.e. rare nonsense, missense, splice-site acceptor or donor variants, exonic indels [36]). There are many algorithms which predict the functional effect of these variants (Table 3).…”
Section: Stage 2 – Filtering/ranking Of Variantsmentioning
confidence: 99%
“…After all the filtering steps in the above figure are applied, the total will be reduced to a single candidate. The numbers here are for illustration purposes only (adapted from [36]). Homozygosity step is added as PCD is an autosomal recessive disorder.…”
Section: Stage 3 – Building Evidence For Causalitymentioning
confidence: 99%
See 1 more Smart Citation